2012
DOI: 10.1038/nature11538
|View full text |Cite
|
Sign up to set email alerts
|

Melanomas resist T-cell therapy through inflammation-induced reversible dedifferentiation

Abstract: Adoptive cell transfer therapies (ACTs) with cytotoxic T cells that target melanocytic antigens can achieve remissions in patients with metastatic melanomas, but tumours frequently relapse. Hypotheses explaining the acquired resistance to ACTs include the selection of antigen-deficient tumour cell variants and the induction of T-cell tolerance. However, the lack of appropriate experimental melanoma models has so far impeded clear insights into the underlying mechanisms. Here we establish an effective ACT proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
571
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 542 publications
(607 citation statements)
references
References 42 publications
31
571
0
5
Order By: Relevance
“…2 In addition, TNF triggered melanoma dedifferentiation, promoting melanoma relapse in an adoptive CD8+ T cell transfer protocol. 3 We have recently demonstrated that TNF signaling facilitates the tumor growth of mouse melanoma exhibiting a high-expression level of major histocompatibility class I (MHC-I high ), while having no or minimal effects toward mouse melanoma expressing MHC-I at low levels (MHC-I low ). As a matter of fact, we provided evidence that the tumor growth of MHC-I high , but not that of MHC-I low melanoma, was impaired in TNF-deficient mice.…”
Section: Introductionmentioning
confidence: 99%
“…2 In addition, TNF triggered melanoma dedifferentiation, promoting melanoma relapse in an adoptive CD8+ T cell transfer protocol. 3 We have recently demonstrated that TNF signaling facilitates the tumor growth of mouse melanoma exhibiting a high-expression level of major histocompatibility class I (MHC-I high ), while having no or minimal effects toward mouse melanoma expressing MHC-I at low levels (MHC-I low ). As a matter of fact, we provided evidence that the tumor growth of MHC-I high , but not that of MHC-I low melanoma, was impaired in TNF-deficient mice.…”
Section: Introductionmentioning
confidence: 99%
“…These barriers include apoptosis and immune recognition. Tumors can also change their protein expression patterns in the course of immune therapy in such a way as to increase their resistance to such therapies (Landsberg et al 2012). As cancer researchers Gatenby and Gillies (2008, 56) recently put it, "Somatic evolution of invasive cancer can …be viewed as a sequence of phenotypical adaptations to these barriers.…”
Section: Objections and Repliesmentioning
confidence: 99%
“…C and CD8 C T-cell proliferation (n D 7). (B) DCs that egressed from the skin biopsies after injecting either wild-type or MART-1 expressing apoptotic cell remnants (ACRs) or blebs, were co-cultured with a MART-1 [26][27][28][29][30][31][32][33][34][35] recognizing and HLA-A2 restricted cytotoxic T lymphocyte (CTL) line (> 95% pure) for 24 hours. Antigen-specific activation was determined by deducting the levels of interferon g (IFNg) produced following the injection of wild-type ACRs or blebs from the levels produced after injecting MART-1 expressing apoptotic fractions (n D 3).…”
Section: Intradermal Bleb or Acr Administration Does Not Interfere Wimentioning
confidence: 99%
“…injected in skin explants from HLA-A2 positive donors in the presence of 4/GM, and skin DC were harvested after 48-72 hours. After a subsequent 24 hours of co-culture with a MART-1 [26][27][28][29][30][31][32][33][34][35] recognizing CTL line (HLA-A2 restricted; >95% pure), the supernatant was analyzed for the presence of IFNg, as a measure of cross-presentation of the MART-1 [26][27][28][29][30][31][32][33][34][35] epitope by egressed DC. The MART-1 [26][27][28][29][30][31][32][33][34][35] specific IFNg production was assessed by deducting the IFNg production following a co-culture with DC from wild-type ACR or blebs injected skin, from that secreted after co-culturing with DC from MART-1-transduced ACR or blebs (D IFNg, Fig.…”
Section: Intradermal Bleb or Acr Administration Does Not Interfere Wimentioning
confidence: 99%
See 1 more Smart Citation